Pengaruh Kompensasi Terhadap Produktivitas Karyawan Pada PT. Mutiara Mulia Raya (MMR) Di Tenggarong Seberang - Rani Noor Fitriani; Askiah Askiah; Sofia Ulfa Eka . Hadiyanti (CV. ITTC INDONESIA, 2025)
Employee productivity refers to the ability of employees to complete tasks effectively and efficiently. At PT. Mutiara Mulia Raya, employee productivity is influenced by compensation. This study aims to analyze the effect of compensation on employee productivity at PT. Mutiara Mulia Raya (MMR), located in Tenggarong Seberang, East Kalimantan. The background of this research is based on the importance of compensation as a strategic factor in enhancing workforce productivity. The method used is a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to 88 employees as a sample from a total population of 113 using the Slovin formula. Data analysis was performed using SPSS with a series of statistical tests, including validity, reliability, normality, heteroscedasticity, linearity, simple linear regression, t-test, and Pearson correlation. The results showed that compensation has a positive and significant effect on employee productivity. This is evidenced by a significance value of 0.000 (< 0.05) and a correlation coefficient of 0.730, indicating a strong relationship between the compensation and productivity variables. Thus, improving a fair compensation system, both financial and non-financial, can encourage optimal employee productivity. The study suggests that the company should continue to develop compensation strategies and consider other supporting factors such as work environment, training, and job satisfaction. This research is expected to serve as a reference for human resource management decision-making in the mining contractor industry sector.